A Middle pleistocene (isotope stage 10) glacial sequence in the Stikine River valley, British Columbia - Spooner, Ian S.; Osborn, Gerald D.; Barendregt, H.; Irving, E. (Canadian Journal of Earth Sciences, 1996)
In the Stikine River valley, northwestern British Columbia, glacial and nonglacial sediments are preserved beneath Middle Pleistocene basalt-flow remnants that originated from Mount Edziza. The magnetic polarity is consistently normal, indicating that the sediment and the basalts were probably deposited within the Bruhnes normal polarity chron (<780 ka). The sediments record a regional glacial advance. Initial ice advance in the Coast Mountains blocked the westward drainage of the Stikine River and formed an advance-phase glacial lake. Sediments deposited in this lake form a coarsening-upwards sequence; debris-flow diamicton units that originated from the valley sides are common. The lacustrine sequence culminates in a poorly sorted ice-marginal gravel deposited as ice encroached upon the study area. There is little record of ice retreat. The basalts are deposited on fluvial and (or) glaciofluvial gravels, indicating that postglacial reincision was taking place at the time of eruption. Hence, the sediments were deposited in the glacial period immediately prior to the emplacement of the basalt. Evidence is presented that indicates that glacial conditions occurred between 341 and 352 ka, which corresponds to pre-Illinoian isotope stage 10.